Evaluation of online training to promote peer diffusion of climate change activism in the US - Dayton, Lauren; Scherkoske, Melissa; Countess, Kennedy; Balaban, Ariel; Miller, Jacob; Wang, Jaiye; Schneider, Kristin; Latkin, Carl (Frontiers in Communication, 2024)
Enacting policies to reduce greenhouse gas emissions requires climate change activism (CCA). CCA behaviors include volunteering/donating to organizations addressing climate change and lobbying policymakers. However, effective methods to promote CCA are not well understood. In August 2022, 622 US adults participated in a randomized control trial and one-month follow-up to assess the efficacy of the Climate Change Activism Peer Educator Training Program, a brief one-time training that aims to train people to talk to their social network members about engaging in CCA. Participants reported high levels of satisfaction. The CCA training increased self-efficacy in having conversations about CCA but did not significantly impact the frequency of communicating about or engaging in CCA. Study findings suggest that future CCA interventions target people motivated to take action about climate change for peer educators, tailor training modules to social network characteristics, integrate prompts to reinforce behavior change, and provide easy and specific targets for CCA.